Strategi Promosi Otoritas Jasa Keuangan (OJK) Provinsi Sulawesi Tengah dalam Edukasi dan Perlindungan Konsumen di Kota Palu - Ermawati, Ermawati; Pakawaru, Irham (State Institute of Islamic Studies (IAIN) Palu, 2016)
OJK presence was a turning point to the many cross issues in the financial services sector which includes measures of moral hazard, financial services consumer protection is not optimal, and the disruption of the stability of the financial system. OJK as an independent institution requires maximum effort promotions on tasks and functions to the public. This research uses descriptive qualitative research to explore strategies of promotion done by OJK of Central Sulawesi Province. The results of this study indicate that, promotion strategies undertaken by the OJK Central Sulawesi province are through is through ads in print and electronic media. Namely periodical published in Radar and Mercusuar newsletters, Billboards installed periodical in the streets of Mayor in the city of Palu, Cinema advertising, Published inÂ XXI Palu Grand Mall and Radio advertising: RRI. While the implications of the implementation of promotional strategies that people are starting to know the whereabouts of the OJK Central Sulawesi province, although not yet familiar with the tasks and functions in educating and providing consumer protection